Intelektual Muslim Abad XX: Peran dalam Pembaharuan Pendidikan Islam di Indonesia - Uswatun Hasanah; Muhamad Bisri Mustofa; Muhammad Saidun Anwar (KURAS Institute, 2022)
This study aims to determine the role of Muslim intellectuals in the 20th century in reforming Islamic education in Indonesia. The figures that the author examines are Hasyim Asy'ari and Ahmad Dahlan a scholar who founded a large Islamic organization. The progress of Islamic education in Indonesia allegedly coincided with the establishment of large organizations, namely Nahdlatul Ulama (NU) and Muhammadiyah. The research method used in writing is descriptive qualitative research by analyzing relevant written data through heuristic methods. In this study, it was found that at the beginning of the 20th century, Indonesian society was a society that was still underdeveloped in terms of knowledge so Dutch influence dominated, the ulema or kiyai made efforts to awaken and educate the Indonesian nation from scientific backwardness to fight against the colonialists. Hasyim Asy'ari and Ahmad Dahlan played an important role in overhauling the Islamic education system in Indonesia. If Hasyim Asy'ari emphasized the ethics and spirituality of Muslims, Ahmad Dahlan made improvements in terms of method and curriculum. The role of the two kiyai has brought major changes to this day. The establishment of Islamic boarding schools, madrasa, and the function of mosques as universities cannot be separated from the role of the two.